Razširjenost prijateljstva v nekaterih slovenskih organizacijah - Koporec Oberčkal, Aleksander (Psihološka obzorja (Ljubljana), 2006)
In Internet based research, Workplace Friendship Scale was used as a measure of two dimensions of friendship, namely opportunities and prevalence. Four hundred forty employees from different organizations in Slovenia participated in research. On the opportunities dimension the results showed differences between organizations, between educational levels, and between leadership functions. The gender structure of co-workers was related to the score on the prevalence dimension. Some gender differences were found on both dimensions. The paper extends knowledge about friendship at working place and in organizations; in addition it confirms previous findings. Paper shows humans as social beings, who are motivated for formation of friendly bonds. At workplace, these bonds can contribute to better work accomplishments, more homogeneity in working groups, more affiliation to organization, and better identification with organizational goals, strategy and mission.
Keywords: delovna mesta; organizacije; prijateljstvo; psihologija